2023
DOI: 10.1111/1365-2435.14255
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms of hosts and their gut microbiomes: Implications for animal physiology and ecology

Abstract: 1. Daily light-dark cycles shape the circadian physiology and behaviour of nearly all organisms, with variation in circadian phenotypes having cascading effects on individual fitness, species interactions and species co-evolution.2. Recent evidence that circadian rhythms in host immunity and metabolism are synchronised by the gut microbiota suggest that the circadian dynamics of gut microbes are a crucial component of their function. However, there remains little knowledge or understanding of the diurnal dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 118 publications
1
6
0
Order By: Relevance
“…Such processes in shorebirds are also observed during summer weight gain in hibernating bears, highlighting the influence of the microbiome in shaping core survival processes of multiple host species (Sommer et al 2016 ). These data thus support the hypothesis that the migratory process is a disturbance, albeit an extreme one, leading to changes in the selective pressures on a community, which in turn result in compositional shifts in the microbiota (Schmid et al 2023 ). Nonetheless, as stated above, with successive migratory events the ‘average’ habitat becomes closer to the migratory habitat—which may result in movement-associated changes falling within the intermediate disturbance hypothesis.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Such processes in shorebirds are also observed during summer weight gain in hibernating bears, highlighting the influence of the microbiome in shaping core survival processes of multiple host species (Sommer et al 2016 ). These data thus support the hypothesis that the migratory process is a disturbance, albeit an extreme one, leading to changes in the selective pressures on a community, which in turn result in compositional shifts in the microbiota (Schmid et al 2023 ). Nonetheless, as stated above, with successive migratory events the ‘average’ habitat becomes closer to the migratory habitat—which may result in movement-associated changes falling within the intermediate disturbance hypothesis.…”
Section: Introductionsupporting
confidence: 83%
“…Although microbial communities are highly dynamic, and have been observed to undergo daily (Zarrinpar et al 2014 , Zhang et al 2023 ) or seasonal cycles (Huang et al 2022 , Schmid et al 2023 ), there remains strong evidence for priority effects on microbial communities (Martínez et al 2018 , Leopold and Busby 2020 ). However, the influence of priority effects may be linked to both the degree of disturbance induced by long distance movements (e.g.…”
Section: A Framework For Microbiome Interactions With Long-distance M...mentioning
confidence: 99%
“…For example, a study on wild meerkats showed that diurnal shifts in GM composition outweighed an association between the GM and host chronological age [33]. Circadian GM dynamics have been identi ed in human and wild animal studies, and may be driven by differences in foraging regimes and dietary intake throughout the day [33,92]. In the Seychelles warbler, the genera Lactococcus and Enterococcus showed the largest increases in abundance between samples collected in the morning and afternoon.…”
Section: Discussionmentioning
confidence: 99%
“…In the Seychelles warbler, the genera Lactococcus and Enterococcus showed the largest increases in abundance between samples collected in the morning and afternoon. Both genera are lactic acid producing bacteria and play an important role in dietary carbohydrate fermentation [93]; as such, these genera may gradually increase in response to an in ux of nutrients as individuals start to forage [92]. However, both genera are also found in insect microbiomes [94][95][96] and so it is possible that these taxa accumulate passively as feeding increases throughout the day and are mainly transient colonisers of the GM that don't carry out a fermentative function.…”
Section: Discussionmentioning
confidence: 99%
“…Data on infection intensity may help distinguish between chronic and acute infections, which is relevant for shaping the type of immune response mounted by the host. Similarly, the order of infections may play a role in how sequentially co-infecting pathogens interact with each other, host immunity and microbiota (Halliday et al, 2017), and certain immune parameters are particularly important for host control over both the gut microbiota and pathogen dynamics (Schmid et al, 2023). Bank voles are an ideal model organism to study these processes experimentally and in the wild because they host a range of pathogens, which differ in the duration and intensity of infection and their transmission ecology, including those that are likely co-transmitted or sequentially transmitted from the same vector (Moutailler et al, 2016).…”
mentioning
confidence: 99%